O polimorfismo do gene p5372(RP) no câncer de cabeça e pescoço: estudo de associação e meta-análise - SILVA, Antonio Márcio Teodoro Cordeiro (2009)
Head and neck cancer arises in the oral cavity and nearby regions, larynx, pharynx, including oropharynx, nasopharynx, and hipopharynx. Extensive epidemiologic studies have revealed that chronic tobacco smoking and alcohol consumption as the two main risk factors associated with the multifactorial etiology of head and neck cancers. Additionally, nutritional status, HPV infection, and genetic polymorphism were also related with the disease. A frequently studied polymorphism in Squamous Cell Carcinoma (SCC) of head and neck is a G-to-C SNP (Single Nucleotide Polymorphism) at codon 72 in the p53 gene, which codes for an Arg or Pro (Arginine or Proline) in P53 protein. In order to investigate the distribution and potential association of that SNP in SCC, biological samples were obtained from 331 cases of head and neck SCC from Araújo Jorge Hospital and 271 healthy control individuals from Goiânia (Brazil) population. DNA was isolated and subsequently used for PCR amplification to genotype cases and controls with respect to their p5372 SNP. Additionaly, a meta-analysis was carried out using 29 relevant case-control studies that used p5372 SNP genotyping in SCC of the head and neck. Allelic frequencies for cases were 73.3% and 27.7% for Arg and Pro, respectively. On the other hand, control allelic frequencies were 74.2% and 25.8% for Arg and Pro, respectively (p = 0.119). Genotypic frequencies were 56.8% Arg/Arg, 32.9% Arg/Pro, and 10.3% Pro/Pro for all cases. The control genotypic frequencies were 61.3% Arg/Arg, 25.8% Arg/Pro and 12.9% Pro/Pro (p = 0,137). According to the current data and meta-analysis, no association between p5372 SNP and the development of SCC of the head and neck was found. Although, the homozygous genotype Arg/Arg was found as an important oncogenic risk factor associated with the carcinoma of the oropharynx.